A Systematic Review of Human Resource Management Systems and Their Measurement. (July 2019) - Boon, Corine; Den Hartog, Deanne N.; Lepak, David P.
In the strategic human resource (HR) management literature, over the past three decades, a shared consensus has developed that the focus should be on HR systems rather than individual HR practices because the effects of HR practices are likely to depend on the other practices within the system. Despite this agreement, the extent to which the fundamental assumption in the field of interactions and synergy in the system holds true is unclear. We present a systematic review of 495 empirical studies on 516 HR systems in which we analyze the development of HR systems research over time and identify important trends, explicitly linking conceptualization and measurement of the HR system. Our findings suggest that the increasingly broad conceptualization and measurement of HR systems and the lack of clarity on the HR systems construct at different levels have hampered research progress. Much of the research to date does not align with the fundamental assumption of synergies between HR practices in a system, the measures have problems and increasingly confound HR systems with related concepts and outcomes, and insufficient attention is paid to the HR system construct at different levels. Overall, we thus still know little about the "systems" element and how synergies and interactions in an HR system operate. We offer actionable suggestions on how to advance HR systems research towards conceptual clarity and construct refinement, focusing both on how to conceptualize, measure, and combine practices in systems and on studying such systems at different levels of analysis.